2019
DOI: 10.1089/heq.2018.0076
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Barriers to Cervical Screening Among Pacific Women: A Narrative Review

Abstract: Purpose: This narrative review explores the barriers and facilitators for Pacific women accessing the cervical screening pathway. Despite organized cervical screening in New Zealand, Pacific women still face significant health disparities in regard to cervical cancer incidence and mortality and access to colposcopy services. Providing a narrative synthesis of the available literature examining Pacific women and the barriers and facilitators to the cervical screening pathway may provide some insight into the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Women deserve to be nurtured throughout the entire pathway and be informed so they are not put off this new screening pathway (and technology). As asserted by previous research, culturally appropriate health promotion campaigns are vital to provide the public with information about changes to cervical screening pathways 5,28,29,36 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Women deserve to be nurtured throughout the entire pathway and be informed so they are not put off this new screening pathway (and technology). As asserted by previous research, culturally appropriate health promotion campaigns are vital to provide the public with information about changes to cervical screening pathways 5,28,29,36 …”
Section: Discussionmentioning
confidence: 95%
“…As asserted by previous research, culturally appropriate health promotion campaigns are vital to provide the public with information about changes to cervical screening pathways. 5,28,29,36 Attending colposcopy was often stressful or uncomfortable for these women. Emotional and material support to help them attend were considered important, as was being treated sensitively by colposcopy teams.…”
Section: Discussionmentioning
confidence: 99%
“…Of those who made an appointment, nearly a third did not attend the primary care practice setting. There are known barriers to primary care access in Aotearoa, New Zealand [34][35][36][37]. The focus groups led to the highest uptake of self-sampling, and in discussions about their experience of the current screening programme, some Pacific women indicated that they would prefer to discuss and attend a screening in a group setting.…”
Section: Discussionmentioning
confidence: 99%
“…4 Self-testing reduces a range of barriers to screening. [5][6][7] Our research and other local studies have demonstrated that self-testing is acceptable, improves participation in screening and will improve equity if well implemented. [8][9][10] We have shown that very overdue and never-screened Māori, Pacific and Asian women were more likely to accept offer of a mailed self-test kit than the same offer in a clinic and, further, that these groups of women have a strong preference for a mailed self-test method of delivery.…”
Section: Discussionmentioning
confidence: 67%